Przekład omówiony, czyli o statusie i funkcji paratekstu (na przykładzie serii Biblioteka Duchowości Europejskiej) - Lis-Wielgosz, Izabela (Przekłady Literatur Słowiańskich, 2017)
Discussed Translation: On the Status and Function of Paratext in the series Library of European Spirituality The article discusses the status and function of paratext based on theseries of trans lations titled Biblioteka Duchowości Europejskiej (Library of European Spirituality). The series itself has been initiated by the Polish Paleo-Slavic community and was published more than ten years ago. The article’s authoress refers to the definition and classification of paratext elaborated on by Gérard Genette, which has been applied to considerations over translation studies for a long time and served as the basis for distinguishing strategies selected by translators as well as identifying the reception space. In the discussion on paratext, the role of the author of a translation is also taken into account, especially the issue of his or her presence, namely: the translator’s visibility, intentionality, and subjectivity revealed by his or her choices. The reflection made on paratexts, which regards only one series, does not exploit the complicated matter of the problem — it rather inscribes itself into the broader discussion which seems neither to exhaust the subject nor to provide satisfaction, since it forces the researcher to face the field demanding other explorations and contemplations. Yet even this general or superficial outline of the problem exposes or confirms the academic arrangements concerning usefulness and functionality of paratext in the process of translating literary works from one system to another. The article also postulates that translation should be incorporated in the space of destination culture, which may assure the translator (the secondary author) full reception of their text, thus allowing the translator’s work to come nearer to the primary reception namely, to assimilate to the process occurring in the realm of departure culture. Keywords: translation, paratext, reception space, translator, series, Library of European Spirituality, Slaviae Orthodoxae